Project Work as the Central Part of the Curriculum - Vargas B. Nohra; Abouchaar V. Alberto (Profile: Issues in Teachers' Professional Development)
The rhythm of social change in the present world is so quick that it is difficult to assess what is needed in the near future. These accelerated changes have crucial implications in education and lead to focusing our teaching on helping learners
develop skills that are essential to obtaining, organizing and using information. Skills that help learners control their lives and learning.